2011
DOI: 10.1111/j.1398-9995.2011.02635.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients suffering from non-IgE-mediated cow’s milk protein intolerance cannot be diagnosed based on IgG subclass or IgA responses to milk allergens

Abstract: Cow's milk protein intolerant patients cannot be distinguished from persons without cow's milk protein intolerance on the basis of IgG subclass or IgA reactivity to cow's milk allergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
4
24
1
1
Order By: Relevance
“…Our data revealed that the IgG3 recorded the highest positive rate, followed by IgG2, IgG1, and IgG4 sequentially. These results were in accordance with previous studies reporting that milk casein elevated the IgG3 and IgG1 levels [23,24]. Hvatum pointed out that IgG3 and IgG1 antibodies were potentially inflammatory.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our data revealed that the IgG3 recorded the highest positive rate, followed by IgG2, IgG1, and IgG4 sequentially. These results were in accordance with previous studies reporting that milk casein elevated the IgG3 and IgG1 levels [23,24]. Hvatum pointed out that IgG3 and IgG1 antibodies were potentially inflammatory.…”
Section: Discussionsupporting
confidence: 95%
“…The diagnostic value of specific IgG antibodies against cow milk proteins (CMP) is controversial because the production of these antibodies is a normal physiologic response following exposure to CMP [22]. Hochwallner et al found that cow milk protein intolerance patients couldn't be distinguished from persons without cow milk protein intolerance on the basis of IgG subclass or IgA antibody levels to purified recombinant alpha S1-casein, alpha S2-casein, beta-casein, kappa-casein, alpha-lactalbumin, and beta-lactoglobulin [23]. Anthoni et al found that milk protein IgG but not milk IgA seemed to be associated with self-reported milk-induced gastrointestinal symptoms [22].…”
Section: Discussionmentioning
confidence: 98%
“…In the area of nonimmediate CMA, Hochwallner et al [12] examined whether patients suffering from non-IgE-mediated cow's milk protein intolerance can be distinguished from persons without cow's milk protein intolerance based on serological measurement of IgG and IgA specific for purified cow's milk antigens utilizing purified recombinant aS1-casein, aS2-casein, b-casein, k-casein, a-lactalbumin and b-lactoglobulin in patients with IgEmediated CMA, with non-IgE-mediated cow's milk protein intolerance, with gastrointestinal symptoms not associated with cow's milk ingestion and in control persons without gastrointestinal problems. They found that only patients with CMA had IgE antibodies to cow's milk and that they mounted the highest IgG(1) and IgG(4) antibody levels to aS1-casein, aS2-casein, b-casein, k-casein and a-lactalbumin and that IgG subclass or IgA reactivity to cow's milk allergens cannot distinguish cow's milk protein intolerant patients from persons without cow's milk protein intolerance.…”
Section: Advances In the Area Of Diagnostics For Cow Milk Allergy Andmentioning
confidence: 99%
“…All patients with the exception of healthy persons reported various symptoms not limited to the gastrointestinal tract, while the patients from the first two groups clearly associated the complaints with the consumption of cow's milk. In the course of the study, the authors determined that there were no differences in sIgG levels in subclasses 1–4 between the patients intolerant to cow's milk protein and the patients who tolerated it [14]. In addition, they noticed that only the patients with IgE-mediated allergy to milk had high levels of IgG1 and IgG4.…”
Section: The Role Of Igg Antibodies In Food Allergymentioning
confidence: 99%